The book of Deuteronomy - Craigie, Peter Campbell, 1938-1988 (Grand Rapids, MI : Eerdmans, 1976)
Includes bibliographical references and indexes.
Includes bibliographical references and indexes.
Keywords: Bible. -- commentaries